Energy and its role in economic development geographical study (Journal of Libya for geographical studies, 2023)
Energy is a motive for improving economic growth, and this research aims to study the importance of energy and its role in economic growth, and its implications for development in Libya. supplies of petroleum products, and that the decline in oil prices in Libya was a cause of a decrease in state revenues, which confirms the diminishing of its future role in the development of its economies. economic performance.
Keywords: energy geography; electric energy; economic growth; economic development